Meningkatkan Kepuasan Pelanggan Melalui Knowledge Management Dan Service Quality - Yakup Yakup (Universitas Gorontalo, 2018)
The purpose of this study was to determine the effect of knowledge management and service quality to customer satisfaction. The research was done at the University of Gorontalo by using a population of 147 students as respondents. Sampling techniques in this study using the proportional method possible random samples from six faculties. The analysis was performed with the Structural Equation Model (SEM) using Lisrel 8,70. The results of the research findings of research showed a positive influence knowledge management and service quality to customer satisfaction. The dominant variable effect on customer satisfaction is a variable service quality.